LEGAL ANALYSIS OF SPPG COMPLIANCE IN THE IMPLEMENTATION OF THE MBG PROGRAM: A CASE STUDY OF SPPG CINTAKU SILEBU - Fiqri Nugraha; Irma Maulida (Hukum Responsif, 2027)
Background. This study examines the legal compliance of the Nutrition Fulfillment Service Unit (SPPG) in implementing the Free Nutritious Meal (MBG) Program, with a particular focus on SPPG Cintaku Silebu. Although the MBG Program is supported by comprehensive technical guidelines issued by the National Nutrition Agency, empirical evidence on implementing agencies' legal compliance and its implications for program governance remains limited. Methods. Employing an empirical legal research approach, this study collected data through document analysis, in-depth interviews with key stakeholders, and direct field observations. Result. The findings indicate that SPPG compliance is influenced by several interrelated factors, including administrative capacity, human resource competence, regulatory understanding, funding adequacy, and the availability of supporting infrastructure. SPPG Cintaku Silebu generally demonstrates satisfactory compliance with operational standards, particularly in food safety, hygiene, and routine monitoring practices, thereby contributing to effective program implementation and legal certainty. However, several challenges persist, including delayed funding disbursement, inadequate facilities, inconsistent interpretation of technical guidelines, and limited institutional capacity, all of which may hinder full compliance and increase administrative and legal risks. Conclusion. From a legal perspective, strengthening compliance through clearer regulatory frameworks, enhanced supervision, continuous capacity building, and improved coordination is essential to ensure accountability and the sustainable implementation of the MBG Program. Implementation. This study contributes to the growing body of literature on public program governance by providing empirical evidence on legal compliance within Indonesia's national nutrition policy and offers practical recommendations for policymakers, regulatory agencies, and program implementers.